Investigation of Killer Cell Immunoglobulin‐Like Receptors KIR2DL2 and KIR2DL3 Diversity and Identification of Ten Novel KIR2DL3 Alleles in the Chinese Han Population. (April 2015) - He, Y.; Tao, S.; Ying, Y.; He, J.; Zhu, F.; Lv, H.
Abstract: KIR2DL2 and KIR2DL3 are important inhibitory receptors that recognize a subset of HLA‐C allelic products carrying Ser77 and Asn80. In this study, we have determined KIR2DL2 and KIR2DL3 diversity in the Chinese Han population by a PCR sequence‐based typing. Based on sequencing, the coding regions of 166 Chinese Han individuals, seven new polymorphic sites (238G>A, 405G>A, 476A>G, 550G>A, 608G>A, 789T>C, 947T>C) were found. KIR2DL2*00301, *00101, KIR2DL3*00101, *00201, *013, *015 and ten new KIR2DL3 variants ( KIR2DL3*00105, 00106, 00107, 00108, 019, 020, 021, 022, 023 and 024 ) were identified, of which KIR 2DL3*00101 was the most frequent allele. Compared with the sequences of KIR2DL3*00101, all sequences of 2DL3*00105, 2DL3*00106, 2DL3*00107 and 2DL3*00108 had one nucleotide substitution(789T>C, 261C>T, 489G>A and 405G>A), but none resulted in amino acid change. An A>G substitution was observed in nucleotide position 476 in 2DL3*019, 608 G>A in 2DL3*020, 824T>C in 2DL3*021 and 238 G>A in 2DL3*023. In addition, 2DL3*022 probably arose from 2DL3*00201 with a nucleotide substitution G>A at 550. There were more HLA‐C1 positive individuals than HLA‐C2. In conclusion, the data of allelic polymorphism for KIR2DL2 and KIR2DL3 were obtained in the Chinese Han population and ten novel KIR2DL3 alleles were identified.